2013
DOI: 10.1007/s11356-013-1530-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide generation in denitrifying phosphorus removal process: main causes and control measures

Abstract: Despite the many benefits of denitrifying phosphorus removal process, the significant generation of nitrous oxide (N2O), a potent greenhouse gas, remains a problem for this innovative and promising process. To better understand and more effectively control N2O generation in denitrifying phosphorus removal process, batch experiments were carried out to investigate the main causes of N2O generation, based on which the control measures were subsequently proposed. The results showed that N2O generation accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…In the study of Oehmen et al (2010), similar phenomenon was also reported but was not emphasized. However, the phenomenon was different from other previous studies in DNPAO systems, where during the anoxic phase, denitrification of nitrate was accompanied with the nitrite accumulation (such as Li et al, 2013b andWang et al, 2011a). , while the NOx-N reduction rate was around 6.0 mg g VSS -1 h -1 under all conditions.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the study of Oehmen et al (2010), similar phenomenon was also reported but was not emphasized. However, the phenomenon was different from other previous studies in DNPAO systems, where during the anoxic phase, denitrification of nitrate was accompanied with the nitrite accumulation (such as Li et al, 2013b andWang et al, 2011a). , while the NOx-N reduction rate was around 6.0 mg g VSS -1 h -1 under all conditions.…”
Section: Resultscontrasting
confidence: 99%
“…The last reason could be due to the competetion among the denitrifying reductases. Li et al (2013b) obtained that N2O generation accounted for 0.41% of the total nitrogen removal in denitrifying phosphorus removal process and the weak competition of N2O reductase for electrons and the high nitrite accumulation were the two main reasons causing N2O generation. The same group also obtained that N2O emission increased with increasing the organic carbon concentrations, which could be due to that a high concentration of organic carbon induced a high production of PHA and consequently a high concentration of accumulated nitrite (Li et al 2013a).…”
Section: Nitrous Oxide Emission Depending On the Type Of Electron Accmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for the high N 2 O production during this period was that DPAOs use PHA as a carbon source for denitrification. Compared with the external carbon source, the rate of PHA degradation is slow, which cannot provide enough electrons for the requirement of denitrifying enzymes, and N 2 O reductase has a weak competition for electrons (Kampschreur et al, 2009;Li et al, 2013a). As a result, N 2 O reduction will be inhibited.…”
Section: Reactor Performance and N 2 O Productionmentioning
confidence: 99%
“…Moreover, it was reported that iron could induce N 2 O emission by enhancing the chemical denitrification pathway (Kampschreur et al 2011). Under lowoxygen condition of SNDPR system, N 2 O can be produced by many biochemical processes, such as heterotrophic denitrification, nitrifier denitrification, and denitrifying phosphorus removal processes (Jia et al 2013;Li et al 2013). The interactions of iron cycle and nutrient cycle are different to soil ecosystem.…”
Section: Introductionmentioning
confidence: 99%